PERSEPSI MAHASISWA AKUNTANSI TERHADAP LINGKUNGAN KERJA AUDITOR MANAJEMEN - Utama, Abdul Halim; Simanjuntak, Benyamin Eliezer Pascareno; Putra, Dian Febriyanto (Prosiding PESAT, 2013)
This research aims to determine how perceptions of accounting students to the workingenvironment auditor management compared with the area of other work in the field ofaccounting. Data were obtained from 51 accounting students using valid and reliablequestionnaires. The questionnaire consisted of 29 questions related to students'perceptions about the differences between management auditor with other work areas inthe field of accounting in terms of job attributes and 3 demographic questions. Datawere analyzed using multiple regression analysis. Intrinsic value of work, financialrewards/salary, working environment, professional training, professionalacknowledgement, social values, labor market considerations, and personalityfactors/variables simultaneously influence the selection of the management auditor’scareer by accounting students significantly. While partially, financial rewards/salaryand social values factors/variables significantly influence the selection of themanagement auditor’s career by accounting students.